2014
DOI: 10.1097/shk.0000000000000194
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Changes in Hospitalized Patients of Trauma

Abstract: Modern clinical management of the patients sustaining traumatic injuries and thermal burns has resulted in their longer survival, but the clinical and pathological effects of these traumatic injuries over the myocardium have been largely neglected. It is speculated that certain factors such as the inflammatory and degenerative lesions of the heart, prolonged clinical course, and the subsequent stress and strain may play role in hastening the death. In the present study, 125 hospitalized cases of traumatic inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…However in our model, volume resuscitation to baseline LVEDV was not able to restore cardiac function to pre-shock levels. This resultant cardiac dysfunction is increasingly recognized as a key determinant of critical care utilization and survival in trauma patients (10, 23, 24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However in our model, volume resuscitation to baseline LVEDV was not able to restore cardiac function to pre-shock levels. This resultant cardiac dysfunction is increasingly recognized as a key determinant of critical care utilization and survival in trauma patients (10, 23, 24).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that trauma patients have elevated levels of biomarkers of myocardial damage within the first 2 h of injury, and this is associated with increased risks of adverse cardiac events and mortality (8, 9). Cardiac histopathology in non-survivors has shown multiple pathological identifiers of indirect or secondary cardiac injury (10, 11). The pathophysiology and mechanisms of secondary cardiac dysfunction are unknown, with most critical care studies limited to sepsis (12).…”
Section: Introductionmentioning
confidence: 99%
“…However, the concept of an early development of trauma-driven cardiomyopathy, resulting from the posttraumatic systemic inflammatory response remains to be proven and examined in detail. In a recent clinical study, post-injury cardiomyopathy occurred in 20% of the fatal cases after severe trauma and histopathological examination of heart specimens revealed significant myocardial lesions even in the absence of coronary alterations [ 7 ]. Most likely, these changes resulted from the patient’s reaction to ischemia and shock conditions without a direct injurious impact on the heart [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lesions were apparent as early as four hours after injury, and typically located around the left ventricle. Histological changes included subendocardial haemorrhages, interstitial oedema, mononuclear infiltration, coagulative necrosis and evidence of hypoxic injury in the absence of existing coronary disease (19). An older post-mortem study of homicide trauma victims has supported these findings, and revealed myofibrillar degeneration, namely scattered clusters of myocytes with homogeneous eosinophilic transverse bands alternating with areas of fine granulation (20).…”
Section: Trauma Induced Secondary Cardiac Injury In Patientsmentioning
confidence: 96%